A Study On Volatility and Tail Risk of Small-Cap Companies in Comparison to Big-Cap Companies - LIM, LIM SIN YEE SALLY; Ts. Dr. ISAUDIN BIN ISMAIL (Enhanced Knowledge in Sciences and Technology, 2022)
GARCH framework analysis was used to examine the volatility and tail risk of small-cap companies in comparison to large-cap companies. The study focuses on the volatility and tail risk of large-cap companies in comparison to small-cap companies. This study examines three large-cap stocks and three small-cap stocks. Daily closing data, alternatively referred to as return, will be analysed in this study. Correspondingly, the performance of small- and large-cap companies is susceptible to volatility and tail risk. As a result, we compared the volatility factor of small- and large-cap companies. A GARCH approach was used to simulate the volatility of small-cap and large-cap companies. This approach was chosen based on the GARCH(1,1) model’s simplicity. All calculations were performed using the statistical tool RStudio.